2007
DOI: 10.1080/10473289.2007.10465340
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Carbon Dioxide/Methane Emissions and the Water Quality/Sediment Characteristics of Taiwan’s Main Rivers

Abstract: River and sediment have unique carbon dynamics and are important sources of the dominant greenhouse gases (GHG), carbon dioxide (CO 2 ) and methane (CH 4 were measured in two of the larger rivers in Taiwan, and relevant environmental conditions were recorded. The experimental results indicated that CO 2 emissions from the river were mainly affected by BOD 5 concentrations and the levels of bacteria. CH 4 emissions, on the other hand, were greatly affected by the ORP in the river. The correlation between CO 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 14 publications
0
2
0
3
Order By: Relevance
“…CH 4 -generating habitats in lakes and wetlands, as well as streams and rivers, share a common trait of having ample stocks of OM that provide the fuel for respiration and allow this process to progress to the point when methanogenesis is the only remaining option. CH 4 concentrations and fluxes are often correlated with sediment OM content (e.g., Wu et al 2007, Baulch et al 2011a, Crawford et al 2014b, and analysis of MethDB revealed a positive relationship between concentration and DOC (Fig. 7).…”
Section: Proximate Controlsmentioning
confidence: 95%
“…CH 4 -generating habitats in lakes and wetlands, as well as streams and rivers, share a common trait of having ample stocks of OM that provide the fuel for respiration and allow this process to progress to the point when methanogenesis is the only remaining option. CH 4 concentrations and fluxes are often correlated with sediment OM content (e.g., Wu et al 2007, Baulch et al 2011a, Crawford et al 2014b, and analysis of MethDB revealed a positive relationship between concentration and DOC (Fig. 7).…”
Section: Proximate Controlsmentioning
confidence: 95%
“…CH 4 concentrations and fluxes are often correlated with sediment OM content (e.g., Wu et al. , Baulch et al. , Crawford et al.…”
Section: A Framework For Controls On Ch4 In Streams and Riversmentioning
confidence: 99%
“…Hal ini sesuai dengan dugaan bahwa tingginya kebutuhan oksigen kimiawi menunjukkan tingginya kandungan material organik/anorganik yang ada di dalam air. Tingginya konsumsi oksigen tersebut terkait dengan kenaikan produk respirasi berupa CO2 (Wu et al, 2007). Salah satu penyebab penurunan pH air adalah kuantitas gas CO2 di dalam air yang kemudian akan menghasilkan ion hidrogen (H + ) dan bikarbonat (HCO3) (Talling, 2010;Raju et al,2014).…”
Section: Pengaruh Kenaikan Cod Terhadap Penurunan Ph Air Sungai Brantunclassified